Numerical Analysis of the End-Suspended Pile and the Rock-Socketed Pile Bearing Capacity of a Soil-Rock Composite Foundation Pit - Xiaobo Xing; Xiangyang Li; Wei Li; Tu Lu; Xiaofeng Duan; Qing Jin (Advances in Civil Engineering)
The bearing capacity of the rock-socketed part of the end-suspended pile and rock-socketed pile was investigated. Numerical models have been partially established with half of the pile and half of the pile space to simplify the model and reduce the number of elements. The strain-softening model was adopted for the rock mass, and the Coulomb friction model was used to simulate the friction between the pile and the soil. Subsequently, the stress deformation and bearing capacity were obtained in the numerical simulation analysis. Finally, the effects of the different support structures, rock-socketed depth, diameter, spacing, and rock shoulder width on piles were analyzed. The numerical results show that both the ultimate bearing capacity and the antideformation capacity of the end-suspended pile are lower than those of the rock-socketed pile. The bearing capacity of both the end-suspended pile and rock-socketed pile increases with an increase in rock-socketed depth, diameter, and spacing. In addition, the performance of the end-suspended pile is also positively correlated with the rock shoulder width.